The appropriation of streets in Belo Horizonte by contemporary carnival blocks | A apropriação das ruas de Belo Horizonte pelos blocos de carnaval contemporâneos - Dias, Paola Lisboa Codo (Revista Brasileira de Estudos Urbanos e Regionais, 2015)
Carnival blocks (roving carnival street parties) in Belo Horizonte have emerged ever since the city was first founded in the late nineteenth century. However, during the 1930s, this kind of carnival manifestation went into decline and lost its importance. During the 1990s, Belo Horizonte became known for its quiet, peaceful streets during the carnival holiday period. However, the first decade of the twenty-first century marked a change in this process during the pre-carnival period, and 2009 marked the beginnings of a movement to re-establish street carnival blocks during the official carnival holiday period. Over the years, carnival in Belo Horizonte has undergone a complete transformation, moving from a decadent festival, marginalized and almost forgotten by most of the population to a very successful effervescent, exuberant celebration. Hence, this article aims to introduce discussions and some unusual perspectives regarding space in the contemporary metropolis with a reflective viewpoint regarding appropriation of the city by carnival celebrations.